Examining vulnerability in a dynamic urban setting: the case of Bangalore’s interstate migrant waste pickers - Michael, Kavya; Deshpande, Tanvi; Ziervogel, Gina (Climate & development, 2019)
Understanding the causality of vulnerability is difficult to do and consequently has received insufficient attention. Root causes of vulnerability need to be understood and addressed to support adaptation that addresses climate risk and inequality. This paper contributes to this by examining vulnerability from a structural perspective for the case of interstate migrants from West Bengal working as waste pickers in Bangalore’s informal squatter settlements. It also throws light on how understanding structural vulnerability can help to emphasize social justice concerns while adapting to climatic risks. The research, using qualitative methods, examines complex intersections between a multitude of factors such as climate change, agrarian distress, exclusionary patterns of urbanization and the resultant lack of recognition that shapes and reshapes the vulnerability of a certain group of people. Our findings emphasize the compelling need for vulnerability and adaptation research to focus more on understanding inequality if improving justice is a concern. This focus on justice is insufficiently prioritized in climate change adaptation work.
Published online: 31 Oct 2018
Gesehen am 17.09.2019